Effects of La2O3-Doping and Sintering Temperature on the Dielectric Properties of BaSrTiO3 Ceramics - Zhao,HongWei (2016)
Using BaCO3, SrCO3 and TiO2, et al as crude materials, La2O3 as dopant, Ba0.8Sr0.2TiO3 (BST) Ceramics of perovskite structure were prepared by solid state reaction method. We investigated the effects of La2O3-doping and sintering temperature on the dielectric properties of BaSrTiO3 ceramics. The experiment results show that: The amount of La2O3 can increase the dielectric constant of the sample, with the doping amount increasing, the dielectric constant increases. The sintering temperature has also significant impact on the dielectric properties. The dielectric constant of the sample reaches its highest point at 1280 °C.